Donor‐acceptor copolymers from cyclopentannulation polymerizations with dicyclopenta[cd, jk]pyrene and dicyclopenta[cd, lm] perylene acceptors. Issue 22 (29th September 2020) - Uddin, Ain; Plunkett, Kyle N.
Abstract: A series of donor‐acceptor copolymers with dicyclopenta[cd, jk]pyrene and dicyclopenta[cd, lm]perylene acceptor units was prepared via palladium catalyzed cyclopenta‐annulation reactions. The acceptor units were paired with diethynyl containing donor groups based on benzo[1, 2‐b:4, 5‐b']dithiophene, thieno[3, 2‐b]thiophene, and 4‐octyl‐4H‐dithieno[3, 2‐b:2′, 3′‐d]pyrrole to create six polymer variants. The cyclopentannulation polymerization resulted in copolymers with molecular weights (Mn) of 6–14 kDa and broad light absorption in the visible region with band gaps of 1.38–1.85 eV. The synthetic methodology, as well as optoelectronic properties, including thin‐film absorption and cyclic voltammetry, of the donor‐acceptor copolymers are presented. Abstract : In this report, a recently described palladium‐catalyzed cyclopentannulation polymerization chemistry is used to create six new donor‐acceptor polymers with dicyclopenta [cd, jk]pyrene and dicyclopenta[cd, lm]perylene acceptor units. The resulting copolymers have reduced band gaps and are unique. They utilize the cyclopentadiene functionality as a mechanism to access low LUMO levels instead of traditional pi‐electron withdrawing groups. The synthetic methodology for monomer and polymer synthesis, as well as the final characterization of the polymers, is detailed.